Study of the strength of monolithic concrete lining of mine shaft under variable heat loads - Bublik, Sergey Anatol’yevich; Semin, Mikhail Aleksandrovich; Levin, Lev Yur’yevich (Computational Continuum Mechanics, 2021)
Monolithic concrete lining is the most popular shaft lining because it is able to endure the rock pressure effects and to exclude large deformations of shaft walls. In the case of starting the reverse ventilation mode in the winter season, a significant negative temperature difference may occur between the warm shaft walls and the cold air from the surface. That temperature difference may have adverse impacts on concrete lining, causing high tensile stresses in it. In this paper, the stress-strain state of the concrete lining and rock mass surrounding the mine shaft is investigated to evaluate the strength of the lining during the reverse ventilation mode in the winter season. The object of the study is the ventilation shaft with surrounding concrete lining and rock mass. Solid and concrete are considered to be isotropic and homogeneous, and their thermodynamic properties are independent of temperature. This allows considering a two-dimensional problem. It is assumed that the temperature drop in lining and rock mass is the only significant factor affecting the stress-strain state of the system. When calculating the temperature of the lining and rock mass, the conductive heat transfer in the volume of rocks and lining, the heat exchange of the lining and rocks with atmospheric air and the heat exchange of the lining with the mine air are taken into account. The presence of moisture in rock mass is not considered. Based on the results of numerical simulation, the following was established. The concrete lining mostly undergoes tensile stresses; the maximum tensile stress acts in a vertical direction. The width of the pre-fracture zone of the lining nonlinearly depends on the duration of the reverse ventilation mode. With an increase in the air temperature in the shaft, the width of the pre-failure zone of the lining decreases, and the permissible duration of the reverse mode significantly increases.
Keywords: mine shaft; concrete lining; temperature deformations; theory of elasticity; strength; numerical simulation